Enhancing Public Knowledge of Sharia Insurance Products in Indonesia Through Effective Management Strategies - Maulana Anwar; Raden Arfan Rifqiawan; Amir Tajrid; Supangat Supangat; Sahidin Sahidin (Universitas Katolik Widya Karya Malang, 2024)
Islamic insurance, known as Sharia Insurance, has emerged as a vital aspect of Indonesia's financial landscape. Sharia Insurance adheres to Islamic economic principles, offering products such as takaful (mutual guarantee) and mudharabah (profit-sharing). The potential for growth in Indonesia's Sharia insurance sector is substantial, bolstered by the country's predominantly Muslim population, which constituted 87.2% of the total population in 2021. Moreover, under Financial Services Authority Regulation (FSAR) Number 11 of 2023, Article 15, Sharia financial institutions are mandated to prioritize Sharia-compliant financial products. Despite these regulatory supports, however, Sharia insurance has achieved only a modest market share, with premiums accounting for just 4.76% as of December 31, 2022. In response to these challenges and opportunities, this study aims to examine the barriers, particularly the issue of public awareness, where many individuals lack a comprehensive understanding and appreciation of the advantages offered by Sharia insurance products. Consequently, this paper addresses two main objectives: 1) identifying factors contributing to public misconceptions and limited awareness of Sharia insurance benefits, and 2) exploring initiatives aimed at addressing these issues. This research employs a qualitative approach, employing systematic literature review techniques to analyze relevant books and literature focused on the identified themes. The findings aim to offer insights into the challenges faced by Sharia insurance and propose strategies to enhance public awareness and understanding of Islamic insurance products.